Synthesis, Characterization and Biologycal Activity of Oxovanadium(IV), Thorium(IV) and Dioxouranium(VI) Complexes of N-(1-pipridinobenzyl)urea and N,N'-bis(N-morpholinobenzyl)urea - Venkatesa Prabhu, G.; Mohamed Kasim, A.N. (Asian Journal of Chemistry, 2010)
The new complexes of oxovanadium(IV), thorium(IV) and dioxouranium(VI) with N-(1-piperidinobenzyl) urea (PBU) and N,N'-bis(N-morpholinobenzyl) urea (MBU) have been synthesised and characterised by elemental analysis, molar conductance, magnetic susceptibility, electronic, IR, 1H NMR and thermal studies. From the IR and PMR spectral data, the ligands, are suggested to behave as O, N donors. PBU coordinates through N atom of piperidine ring and O atom of urea fragment while MBU acts as a tridentate ligand coordinating through N atoms of two morpholine rings and O atom of urea moiety. The complexes have also been screened in vitro for antibacterial activities.